USING DEBATE TO IMPROVE STUDENTS’ VOCABULARY AND SPEAKING ACHIEVEMENTS - Hartini Agustiawati; Ismail Petrus; Margaretha Dinar Sitinjak (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: The purposes of this study were to find out (1) whether there was a significant difference in vocabulary achievement between students who were taught through debate, and those were taught without debate, (2) whether there was a significant difference in speaking achievement between the students who were taught through debate and those were taught without debate, (3) whether there was a significant correlation between vocabulary and speaking achievements of the fourth semester, English education study program students of Tridinanti University and how much the contribution of vocabulary to speaking is. The population of this study consisted of the fourth semester English education study program students of Tridinanti University. The total number of the population was 49 comprising four classes, while the sample consisted of 30 students who were divided into two groups, fifteen students were in the experimental group and another fifteen students were in the control group. In collecting the data, the pretest, treatment and posttest were used. However, the data were analyzed by using t-test. It was found that (1) there was a significant difference in vocabulary achievement where the sig value (2 tailed) was lower than 0.05, (2) there was a significant difference in speaking achievement where the sig value (2 tailed) was lower than 0.05, (3) there was a significant correlation and contribution between vocabulary and speaking. It could be concluded that debate could improve the students‟ vocabulary and speaking achievements.Key words: vocabulary, speaking, and debate, fourth semester students of English Education Study Program